Assessment of nutrition status of pineapple plants during ratoon season using diagnosis and recommendation integrated system - Anh Nguyen Huynh Minh; Hiep Phan Chan; Ngan Nguyen Thanh; Tho Le Thi Ngoc; Trong Nguyen Duc; Thuan Vo Minh; Thien Tran Thi Ngoc; Quang Le Thanh; Khuong Nguyen Quoc (Open Agriculture)
Source: Created by Authors.